DEVELOP INDICATOR FOR ATTRIBUTE OF RATE OF ADOPTION TO AEC ENTRANCE IN PATHUMTHANI PROVINCE - กันอ่ำ วสันต์; ร่างสม กฤติยา (RMUTT Global Business and Economics Review, 2016)
This article presented how to develop indicator for rate of adoption to AEC entrance in Pathumthani province. This is a survey research. The research population was citizens of Pathumthani province. 385 respondents had been collected by questionnaire. The data was analyzed by the exploratory factor analysis and confirmatory factor analysis. The findings indicated that there were 4 components including observability, relative advantage, complexity, and compatibility, extracted by the principal method and varimax rotation. The confirmatory factor analysis showed that the model is consistent with collected data.